Factors Affecting Millennials Consumers in Choosing Airlines to Travel during the Covid-19 Pandemic - Coloay, Berend Gensan; Agung Suprastayasa, I Gusti Ngurah (Jurnal Penelitian Pariwisata, 2022)
The purpose of this study is to figure out the factors that influenced the decision of millennial consumers to choose airlines for traveling during the pandemic. Transportation plays an important role for many people in Indonesia, especially young people or millennials, one of which is air transportation. About the Covid-19 pandemic conditions, it is important to know the factors that affected consumers, especially millennials, in choosing an airline to travel. This could help airline companies to survive the pandemic conditions. This study uses a qualitative method in which data were analyzed using descriptive qualitative analysis. Semi-structured interviews with ten key informants collected the data: four students categorized as millennials, five private sector employees, and one law firm employee. This study showed that price factor influences millennial consumers the most in choosing Airlines for traveling during the pandemic, while environmental factor influences the least. Keywords: Airlines, Travel, Millennial Consumers, Pandemic